Effect of fiber type and thickness on mechanical behavior of thermoplastic composite plates reinforced with fabric plies - Öztekin, Hilal Filiz; Gür, Mustafa; Erdem, Serkan; Kaman, Mete Onur (My University, 2022)
Studies on weight reduction in aviation and space vehicles have gained momentum recently. Thermoplastic matrix composite materials are important alternative materials, especially due to their high specific strength, formability and recyclability. In this study, it is aimed to investigate the mechanical behavior of fiber reinforced thermoplastic composites for different fiber and layer configurations. Thermoplastic composite materials used in the study were produced by lamination technique. In composite production; Glass fiber and carbon-aramid hybrid fabrics were used as fiber, and polyethylene granules were used as matrix. Thermoplastic sheets were obtained by keeping polyethylene granules and woven fibers in the hot press for a certain period of time. The damage behavior of the composite test specimens under tensile load was tested for the number of layers and fiber type. As the number of layers increased, stiffness, damage load and deformations increased in thermoplastic composites. Using hybrid fabric instead of glass as fiber material increased the maximum damage load by 100%.
Keywords: Glass fiber; Polyethylene; Tensile test; Thermoplastic composites; Hybrid woven